ATP/IL‐33‐triggered hyperactivation of mast cells results in an amplified production of pro‐inflammatory cytokines and eicosanoids. Issue 3 (30th June 2021) - Jordan, Paul M.; Andreas, Nico; Groth, Marco; Wegner, Philine; Weber, Franziska; Jäger, Ute; Küchler, Claudia; Werz, Oliver; Serfling, Edgar; Kamradt, Thomas; Dudeck, Anne; Drube, Sebastian
Abstract: IL‐33 and ATP are alarmins, which are released upon damage of cellular barriers or are actively secreted upon cell stress. Due to high‐density expression of the IL‐33 receptor T1/ST2 (IL‐33R), and the ATP receptor P2X7, mast cells (MCs) are one of the first highly sensitive sentinels recognizing released IL‐33 or ATP in damaged peripheral tissues. Whereas IL‐33 induces the MyD88‐dependent activation of the TAK1‐IKK2‐NF‐κB signalling, ATP induces the Ca 2+ ‐dependent activation of NFAT. Thereby, each signal alone only induces a moderate production of pro‐inflammatory cytokines and lipid mediators (LMs). However, MCs, which simultaneously sense (co‐sensing) IL‐33 and ATP, display an enhanced and prolonged activation of the TAK1‐IKK2‐NF‐κB signalling pathway. This resulted in a massive production of pro‐inflammatory cytokines such as IL‐2, IL‐4, IL‐6 and GM‐CSF as well as of arachidonic acid‐derived cyclooxygenase (COX)‐mediated pro‐inflammatory prostaglandins (PGs) and thromboxanes (TXs), hallmarks of strong MC activation. Collectively, these data show that co‐sensing of ATP and IL‐33 results in hyperactivation of MCs, which resembles to MC activation induced by IgE‐mediated crosslinking of the FcεRI. Therefore, the IL‐33/IL‐33R and/or the ATP/P2X7 signalling axis are attractive targets for therapeutical intervention of diseases associated with the loss of integrity of cellular barriers such as allergic and infectious respiratory reactions. Abstract : Co‐sensing of ATP and IL‐33 triggers hyperactivation of mast cells resulting in an amplified production of pro‐inflammatory cytokines and eicosanoids. Imagewas created with BioRender.com.